2013
DOI: 10.1016/j.fgb.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Two β-xylanases from Aspergillus terreus: Characterization and influence of phenolic compounds on xylanase activity

Abstract: Sugarcane bagasse was used as an inexpensive alternative carbon source for production of β-xylanases from Aspergillus terreus. The induction profile showed that the xylanase activity was detected from the 6th day of cultivation period. Two low molecular weight enzymes, named Xyl T1 and Xyl T2 were purified to apparent homogeneity by ultrafiltration, gel filtration and ion exchange chromatographies and presented molecular masses of 24.3and 23.60 kDa, as determined by SDS-PAGE, respectively. Xyl T1 showed highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 32 publications
0
7
1
1
Order By: Relevance
“…Brazil is the second biggest producer of soybean worldwide, harvesting 96.5 kton in 2016, just behind United States, with 106.9 kton in 2016 [ 10 , 11 ]. Therefore, soybean residues represent the major byproduct of processing soybean industry [ 12 ], which could be used as a carbon source for the production of enzymes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is the second biggest producer of soybean worldwide, harvesting 96.5 kton in 2016, just behind United States, with 106.9 kton in 2016 [ 10 , 11 ]. Therefore, soybean residues represent the major byproduct of processing soybean industry [ 12 ], which could be used as a carbon source for the production of enzymes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With previous purification and characterization in A. terreus ( Soni et al, 2016 ), here we observed four CAZyme-encoding DEGs associated with degradation of these polysaccharides. Whilst the pectin content in SB and SH is considerably lower than for hollocellulose ( de Souza Moreira et al, 2013 ; Li et al, 2017 ), evidence was also observed for pectin degradation on both, with considerable exclusive up-regulation of genes on SH likely reflecting differences in pectin content between the different carbon sources. Up-regulation of genes related to pectinolytic activity have also been reported previously on SB for A. niger (PL4 family), A. fumigatus (PL4 family) and for A. tamarii (PL1, PL9, GH28 families) ( Borin et al, 2017 ; de Gouvêa et al, 2018 ; Midorikawa et al, 2018 ).…”
Section: Discussionmentioning
confidence: 92%
“…related to biomass degradation comprise CreA (carbon catabolite repression), within the Cys2His2 class and the HAP complex (Cazy regulation), within the CBF class ( Benocci et al, 2017 and references therein). Whilst mechanisms for regulation of expression of sugar transporter genes during sugar utilization in fungi is only partially understood at present, a number of the above transcription factors, such as XlnR, CreA, ClrA/ClrB, GalX and AraR, are also known to regulate sugar transporter genes in model Aspergillus species (e. g. Vankuyk et al, 2004 ; Andersen et al, 2008 ; de Souza Moreira et al, 2013 ). Our data revealed considerable numbers of transcription factor genes with significant differential expression on SB and/or SH at a probability level of p ≤ 0.01, with 15 at log2 fold change (FC) at least ≥2-fold and 84 at log2 fold change (FC) <2-fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O ácido ferúlico já foi descrito como responsável tanto pelo aumento na atividade da xilanase (XylT2) de Aspergillus terreus (Moreira et al, 2013), quanto pela inibição de celulases comerciais da Novozyme que tem origem de diversos microrganismos (Tejirian e Xu, 2011 (Moreira et al, 2013), e não afetou a atividade de xilanase de CPP. Outra vantagem da amostra CPP, é que ela não teve alteração em suas atividades enzimáticas quando incubada com o ácido 4-hidroxibenzóico, enquanto que esse fenol só foi observado atuando de forma repressora em outras atividades celulolíticas de enzimas comerciais oriundas de diversos microrganismos, descritas anteriormente (Ximenes, 2010;Ximenes et al, 2010a;Tejirian e Xu, 2011).…”
Section: Efeito Dos Compostos Fenólicos Nas Atividades De Cmcases E Xunclassified